2014
DOI: 10.1074/jbc.m114.583518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Innate Immune Response by Varying Dosages of Lipopolysaccharide (LPS) in Human Monocytic Cells

Abstract: Background: Super-low-dose endotoxin causes mild but significant pro-inflammatory skewing. Results: Inhibition of GSK3 or activation of CREB ablates preferential induction of pro-inflammatory genes by super-low-dose LPS. Conclusion: GSK3 is necessary for pro-inflammatory gene induction in response to super-low-dose LPS, acting by activating FoxO1 and suppressing CREB. Significance: Persistent, non-resolving inflammation is a characteristic of many chronic diseases, and this study points toward potential therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 54 publications
7
61
0
Order By: Relevance
“…Similar protection has been observed in ischemia or endotoxin tolerance, in which preexposure to ischemia or lipopolysaccharide results in attenuated tissue injury during subsequent insults (23)(24)(25). The nature of the induced protection and underlying mechanisms of preconditioning are not yet clear, but studies suggest that innate immune cells such as monocytes/ macrophages play a central role (26)(27)(28). Here we found that the MSC preconditioning involved a distinct subset of suppressive MHC II + B220 + CD11b + monocytes/macrophages in the lung.…”
Section: Discussionsupporting
confidence: 79%
“…Similar protection has been observed in ischemia or endotoxin tolerance, in which preexposure to ischemia or lipopolysaccharide results in attenuated tissue injury during subsequent insults (23)(24)(25). The nature of the induced protection and underlying mechanisms of preconditioning are not yet clear, but studies suggest that innate immune cells such as monocytes/ macrophages play a central role (26)(27)(28). Here we found that the MSC preconditioning involved a distinct subset of suppressive MHC II + B220 + CD11b + monocytes/macrophages in the lung.…”
Section: Discussionsupporting
confidence: 79%
“…For example, TLR4 activation elicits the production of cytokines via activating NF-B and MAPKs, it also enhances the expression of the negative regulators IB and MKP-1 which terminate NF-B and MAPKs. TLR4 activation also stimulates the PI3K/Akt pathway, which serve to terminate the inflammatory responses (35). Our finding that TLR activation induces both iNOS and arginase further highlights the intricacy of the regulatory mechanisms at the iNOS level to ensure the balance between activating the antimicrobial immune defense and limiting collateral tissue damage.…”
Section: Arginase Versus Inos In Macrophagementioning
confidence: 63%
“…Acute administration of relatively low doses of LPS (1.0-50.0 g/kg) has been shown to affect burrowing behavior, locomotor activity, social interactions and cognitive processes in mice and rats [18,22,53,60,62]. Low doses of LPS also induce the release of proinflammatory mediators by murine macrophages and have priming effects on subsequent immune challenges in rats [6,20,32,[45][46][47][48]59].…”
Section: Introductionmentioning
confidence: 99%